Representações sociais frente ao abuso sexual contra crianças e adolescentes: culpabilização da vítima e penalidades processuais - Pereira, Camila de Alencar (2020)
The implementation of public policies on sexual abuse against children and adolescents has great influence in the legal area, since it is from the application of the law that the State manifests its preventive and reparative reaction to the person attacked and repressed to the aggressor. The present thesis aims to identify the way the victim of sexual abuse is socially represented, considering the age group variable (child and adolescent), and how these representations have repercussions on judicial decision-making, based on the theory of social representations and in blaming the victim. This thesis was developed in the form of articles, one theoretical and four empirical - all independent, however, constructed in an articulated way in the search to answer the following thesis: the social representation about sexual abuse against children and adolescents varies according to the age group of the victim, in which adolescent victims of sexual abuse are blamed for the violence suffered, anchored in the myth of seduction. Article 1 aimed to carry out a theoretical articulation about sexual abuse against children and adolescents, aspects of the victim's blame and social representations about the phenomenon. Article 2 provides a systematic review of the literature on social representation about sexual abuse against children and adolescents. Through the search, and following the inclusion and exclusion criteria, a total of 13 articles were selected for data extraction. In the extraction of data from these 13 manuscripts, it can be seen that, when studying the social representation of sexual abuse against children and adolescents, some representational aspects are frequent: sexual abuse and treatment, the factors of maintenance and promotion of sexual abuse, the victim and its consequences and the aggressor. There are some gaps in the research already developed on the subject to date. Thus, it is suggested the development of comparative research on the social representation of the victim, in order to investigate whether there is a difference in the way these victims are seen and treated socially. Article 3 aimed to identify and compare the structure of social representation on sexual abuse against children and adolescents. The Free Word Association Technique (TALP) was used, with the stimuli "sexual abuse against children" and "sexual abuse against adolescents". 266 undergraduate students from the psychology and law courses of public and private institutions in Paraíba participated in this study. The data were analyzed with the aid of IRAMUTEQ, through prototypical analysis. The results showed that, when the victim is a child, the participants tend to evoke terms focused on the victim, such as: suffering, trauma, innocence and vulnerability. When the stimulus was adolescent, sexual abuse was portrayed mainly by the act, through evocations: rape, trivialization, violence, unreal / sexualization and blame, which brings us to the idea that sexual abuse against adolescents is more trivialized and the victim be seen as seductive and therefore partly to blame for the violence suffered. It is noticed that when the victim is a child, the representation is more focused on the damage suffered and its fragility, which is not seen when he is a teenager. Considering that social representations guide behaviors and therefore can have an impact on decision-making, it was decided to write Article 4, which addressed the social representations of judges about the sexual abuse of children and adolescents. For this, a semi-structured interview was conducted with 12 first and second instance law judges. With the data, an analysis of Bardin's thematic categorical content was carried out. There was a difference in the way the victim of sexual abuse is seen by professionals, verifying, through the participants' speech, that the physical and postural aspects of the victim were often considered as evaluative and validating criteria of violence suffered, thus promoting the socialization of the attacked person. In the face of such a scenario, the need to ascertain whether social representations influenced judicial decision-making, the object of defense of the present thesis, was perceived. Thus, Article 5 sought to make a comparative analysis of legal cases characterizing victims of sexual abuse, aggressors and penalties applied to the defendant. It was carried out through an analysis of 238 second instance judicial decisions (judgments), observing and comparing, in these, the penalties applied in the first and second instances. Such judgments were obtained through an electronic search on the website of the Court of Justice of Paraíba (TJPB), between the years 2016 and 2018, using the terms “sexual abuse” and “rape of the vulnerable”, opting to work with these descriptors, as the first refers to how the phenomenon is known socially and the second is a terminology commonly used in the legal field. It was observed that, in general, the victim is female and suffers this type of violence at around 10 years of age, being sexually abused by a commonly male aggressor. As a rule, the aggressor is sentenced to 9 years in a closed regime in both instances, a little more than the minimum penalty applied to the crime. It was also found that there is an attenuation in the penalty applied to the aggressor, whose victim was an adolescent, possibly the result of the social representations of these professionals, more specifically the collective understanding of early sexualization as behavior that contributes to the practice of crimes by the aggressors. The different forms of research and the different contexts applied throughout the thesis, allow us to understand that victims of sexual abuse have been represented, within the scope of the theory of social representations, according to their age group. It is observed that there is a common representation for sexual abuse, such as trauma and violence, however, considering their age group, child and adolescent victims are now represented as vulnerable or blamed, respectively. In general, the articulation between the studies of this thesis presents contributions to the understanding of social representations about sexual abuse against children and adolescents and their repercussions in judicial decision-making. The implications of these results should be considered as a contribution to understanding how victims of sexual abuse are seen and treated socially, especially teenagers, who end up being blamed for the violence they suffered. Such findings should serve as a support for the formulation of strategies to reduce the attribution of guilt to victims of sexual abuse, as well as the development of more effective public policies to guide professionals, family members and society as a whole.